2009
DOI: 10.1016/j.bpj.2008.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide-1-Phosphate, in Contrast to Ceramide, Is Not Segregated into Lateral Lipid Domains in Phosphatidylcholine Bilayers

Abstract: Sphingolipids are key lipid regulators of cell viability: ceramide is one of the key molecules in inducing programmed cell death (apoptosis), whereas other sphingolipids, such as ceramide 1-phosphate, are mitogenic. The thermotropic and structural behavior of binary systems of N-hexadecanoyl-D-erythro-ceramide (C(16)-ceramide) or N-hexadecanoyl-D-erythro-ceramide-1-phosphate (C(16)-ceramide-1-phosphate; C(16)-C1P) with 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) was studied with DSC and deuterium nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Studies based on the fluorescence anisotropy have indicated that phospholipids tend to be more ordered in the presence of ceramides [20, 23, 25]; similar observations have been made using NMR, specifically for ceramides with 16-carbon chains, or C16-ceramide, in DPPC and POPC bilayers [21, 22, 27]. …”
Section: Introductionmentioning
confidence: 80%
“…Studies based on the fluorescence anisotropy have indicated that phospholipids tend to be more ordered in the presence of ceramides [20, 23, 25]; similar observations have been made using NMR, specifically for ceramides with 16-carbon chains, or C16-ceramide, in DPPC and POPC bilayers [21, 22, 27]. …”
Section: Introductionmentioning
confidence: 80%
“…30 In the composition of SCLLs, ceramide is the lipid with the highest Tm value which is between 80°C and 90°C. 35 Since panomycocin is irreversibly inactive in this temperature range, we have used a modified freeze-thaw method in which the thawing was done at 4°C under vacuum 30 in order to preserve protein stability. The zeta potential values for empty and loaded liposomes were +22.0 and +21.4 mV, respectively, indicating a very low protein binding on the surface of the liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…32 The high stability is most probably due to the long chain lipids with high phase transition temperatures found in the composition of SCLL structure, and this is also supported by the studies reporting a highly ordered structure and increased phase transition temperature for the lipid bilayers containing ceramides. 35,45 We have performed a biological efficacy test of the liposomal panomycocin formulation on an in vitro model of vaginal candidiasis. Liposomal lyophilized powder with predetermined panomycocin quantities for each Candida spp., which correspond to 1× MFC value of nonformulated pure panomycocin, was found to be inhibitory for all the tested strains.…”
Section: Discussionmentioning
confidence: 99%
“…The binary systems of N-hexadecanoyl-D-erythro-ceramide (C16-ceramide) or N-hexadecanoyl-D-erythro-ceramide-1-phosphate (C16-ceramide-1-phosphate; C16-C1P) with 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) were studied with DSC and 2 H-NMR. 24 The effects of cholesterol on the thermotropic phase behavior and organization of aqueous dispersions of a homologous series of linear disaturated phosphatidylglycerols (PG) was investigated by DSC, FT-IR and and 31 P NMR spectroscopy. The incorporation of increasing quantities of cholesterol alters the temperature and progressively reduces the cooperativity of the gel-to-liquid-crystal phase transition of the host PG bilayer.…”
Section: Thermotropic Liquid Crystalsmentioning
confidence: 99%